Mesoporous Silicon Microparticles Enhance MHC Class I Cross-Antigen Presentation by Human Dendritic Cells - A. Jiménez-Periáñez; B. Abos Gracia; J. López Relaño; C. M. Diez-Rivero; P. A. Reche; E. Martínez-Naves; E. Matveyeva; M. Gómez del Moral (Clinical and Developmental Immunology)
The mesoporous silicon microparticles (MSMPs) are excellent vehicles for releasing molecules inside the cell. The aim of this work was to use MSMPs to deliver viral specific MHC class I restricted epitopes into human antigen presenting cells (monocyte derived dendritic cells, MDDCs) to facilitate their capture, processing, and presentation to CD8+ (cytotoxic) T lymphocytes. We show for the first time that MSMPs vehiculation of antigenic peptides enhances their MHC class I presentation by human MDDCs to CD8 T lymphocytes.